Професійна культура як фактор професійної діяльності юриста - Чупринський, Б.; Chuprynsky, B. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті досліджується процес формування професійної культури майбутніх юристів. Характеризується різноманітні види людської діяльності. Визначено основні компоненти структури професійної діяльності юриста. Здыйснено аналіз поняття «комунікативна компетенція юриста», і її значення в професійній діяльності. Зроблено висновок про те, що професійна культура фундаментально впливає на професійну діяльність юриста, пов'язується з безперервним процесом його виховання, освіти, обумовлена специфікою його юридичної діяльності.The article examines the process of formation of the professional culture of future lawyers and characterizes various types of human activity. The author focuses on the main aspects of the professional activity of the lawyer and provides a comprehensive analysis of the notion «communicative competence of a lawyer», paying attention to the importance of this skill in his professional activity. The key findings of the study argue that professional culture fundamentally influences the professional activity of a lawyer and is associated with the continuous learning process and professional skills development, arising from the specificity of the legal profession. Professional culture is closely connected with the culture of the person, which is characterized primarily by work, activity, performance of duties, and especially their quality because only by high-quality work a person transforms the world and realizes his/her talents, skills, and abilities. Successful lawyer's professional activity requires durable competencies and skills, which are formed under the influence of education, work, and other life activities. Therefore, the system of the future lawyers training in higher education institutions should focus on the theoretical and practical aspects of the future professional activity, which will be a guarantee of high-quality, effective performance of the duties.
Professional Ethics as an Integral Part of the Professional Activity of a Lawyer
Keywords: діяльність; навчальна діяльність; професійна діяльність; юридична діяльність; професійна культура; професійна компетенція; комунікативна компетенція; комунікативні вміння; activity; learning activities; professional activity; legal activity; professional culture; professional competence; communicative competence; communication skills